CLIFF-LAMNET Summer School Course - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (International Center for Tropical Agriculture, 2015)
The new Latin America Greenhouse Gas Mitigation Network (LAMNET) is a regional subsidiary of The Climate Food and Farming Research Network (CLIFF), an international research network that helps to build the capacity of young researchers working on climate change mitigation in smallholder farming.